AB054. An improved technique for bladder cancer: pure laparoscopic radical cystectomy with orthotopic U-shape ileal neobladder using titanium staples - Wang, Shuai (Transl Androl Urol, 2015)
OBJECTIVE: To report our experience with an improved technique of laparoscopic radical cystectomy (LRC) and orthotopic ileal neobladder reconstruction, evaluating the perioperative and pathological outcomes. METHODS: We retrospectively reviewed the data of 56 cases who underwent radical cystoprostatectomy followed by construction of an orthotopic U-shaped ileal neobladder between August 2010 and December 2014. These data include intraoperative data, early and long-term postoperative complications, neobladder function, urinary continence and oncologic results. Also the key innovative procedure was introduced with details. RESULTS: The median time of the overall procedure was 212 min. The median estimated blood loss was 171 mL. The median hospitalization time after the operation was 21 days. Complications included two cases of unilateral ureter-pouch anastomotic strictures, one case of bilateral ureteral stricture, three cases of vesicourethral anastomotic strictures and three cases of vesicourethral leakage. The mean maximum pouch capacity was 446±32 mL, and pouch pressure at capacity was 18.1±2.6 cmH(2)O. The Q(max) was 14±1.2 mL/s, and the mean post-void residual was 25±10 mL. There were nine cases of night-time incontinence at 3 months post-operatively. Negative surgical margins of the bladder specimens were achieved in all patients. During a follow-up period of 3 to 44 months (average 32.6 months), local recurrence was found in two patients and distant metastasis was occurred in another three patients. CONCLUSIONS: Our preliminary experience showed that pure LRC with non-absorbable titanium staples assisted orthotopic U-shape ileal neobladder reconstruction is feasible based on perioperative data and oncologic features.